Hyperpolarization of neuroblastoma-glioma hybrid NG108-15 by vanadium ions. - Lichtstein, D (1982)
Vanadate hyperpolarizes mouse neuroblastoma-glioma hybrid NG108-15 by 20-30 mV. These changes in membrane potential (delta psi) are observed by monitoring the equilibrium distribution (intracellular/extracellular) of the lipophilic cation [3H]tetraphenylphosphonium (TTP+) and by directly measuring delta psi with intracellular microelectrodes. In physiological media (i.e., 135 mM NaCl/5 mM KCl), the half-maximal effective concentrations of sodium orthovanadate (Na3VO4) and sodium metavanadate (NaVO3) are 35 and 160 microM, respectively. The maximal effects for both these ions are quantitatively indistinguishable. The hyperpolarizing responses to vanadate occur without any observable lag, have t1/2 less than or equal to 30 sec, and are always accompanied by simultaneous decreases in membrane resistance. Neither ouabain nor media containing high K (i.e., 120 mM) devoid of Na and K (isotonicity maintained by choline) prevent the change in delta psi induced by vanadate. Therefore, vanadate produces a unique hyperpolarization which does not depend upon Na, K, or the Na/K pump. Furthermore, the accompanying decreases in membrane resistance indicate that vanadate must increase the permeability of the membrane to some ion. Our data are consistent with it being an anion, such as chloride or vanadate itself. Finally, vanadate hyperpolarizes many different types of cultured cells, only some of which are of neuronal origin. This indicates that a hyperpolarization of delta psi must be considered in any assessment of the physiological actions of the vanadates.